UPAYA INDONESIA DALAM MENJADIKAN UBUD SEBAGAI DESTINASI GASTRONOMI MELALUI UNITED NATIONS OF WORLD TOURISM ORGANIZATION (UNWTO) TAHUN 2017-2019 - Albert, Yoel; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research analyzes the Indonesia’s effort to make Ubud as a gastronomy tourism through United Nations of World Tourism Organization (UNWTO) in 2017- 2019. Study of culture and food is gastronomy. Understanding, tasting, experiencing, researching, discovering and writing about the sensory qualities of human nutrition and human preparation is called gastronomy.This research uses a pluralism perspective. Policies can be from different actors. The theory of cultural diplomacy is used to analyze this study. The method used is a qualitative method. The data obtained by doing literature study which consist of books, journal, websites and dissertation.This research shows the result of Indonesia’s effort to make Ubud a gastronomy tourism through United Nations of World Tourism Organization (UNWTO). Cultural diplomacy carried out by Indonesia uses the form of diplomacy in the form of exhibitions, competitions, negotiations and conferences. The forms of diplomacy that have been carried out by Indonesia have resulted in good relations between Indonesian government and UNWTO, and also increasing cooperation between Indonesia and UNWTO in gastronomy. Keywords : Ubud, Gastronomy, UNWTO, Cultural Diplomacy